Pendampingan Desain Media Promosi Sekolah melalui Pendekatan Komunikasi Partisipatif - Mutia Rahmi Pratiwi; Mukaromah Mukaromah; Dzuha Hening Yanuarsari (LPPM UNIVERSITAS DIAN NUSWANTORO, 2022)
The process of forming a brand image to the public takes time. The process of increasing brand awareness can be done by optimizing school promotion media. MI Baiturahhim Semarang is a service partner who needs assistance in the process of optimizing the design and types of promotional media by considering the limitations of the partners. Twibbon can be one of the alternative promotional media that can be used in an easy way and through sharing media such as whatsapp status. Assistance is carried out using participatory communication methods with the initial stages of heteroglasia, dialogic communication, polyphony and the application of the carnival side. Observing the needs of partners in the early stages shows the heteroglasia side of the participants, namely the diversity of teacher origins and knowledge related to media and promotional design. Then in its implementation there is a dialogical communication with both the principal and the teacher. In the implementation stage, knowledge information about media and design is provided, providing hands-on practice with participants related to design and twibbon media so that they are included in the polyphony stage or understanding regarding the given topic. A serious but relaxed mentoring situation in delivering mentoring materials is a form of carnival stage in participatory communication. The results obtained, partners feel the benefits of knowledge about the use of various promotional media, recognize twibbon as a promotional media and design with photoshop software to be uploaded to twibbon media and distributed to whatsapp status.